Adhesive sheet and optical laminate
By using an adhesive composition containing monomer group and polymer, and treating trifluoroethanol on the surface of the adhesive sheet and adding anti-corrosion agent, the corrosion problems when the adhesive sheet contacts the ITO conductive layer and peeling problems in high temperature environments are solved, thereby achieving higher anchoring force and use stability.
Patent Information
- Application Number
- CN202380055630.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-22
- Filing Date
- 2023-07-21
- Publication Date
- 2025-03-11
AI Technical Summary
The conventional adhesive sheet may easily cause corrosion of the conductive layer when contacting the conductive layer containing metal oxides such as ITO. When reused in a high-temperature environment, the anchoring force between the adhesive sheet and the optical film is reduced, and peeling is prone to occur.
Using an adhesive sheet formed of an adhesive composition containing a monomer group and/or a polymer of the above-mentioned monomer group, a surface treatment of trifluoroethanol to increase the element ratio of fluorine, and an anticorrosion agent is added to the adhesive composition to inhibit corrosion of the conductive layer and increase the anchoring force of the optical film.
The corrosion of the conductive layer is effectively suppressed, and the anchoring force between the adhesive sheet and the optical film is improved, reducing the risk of peeling when reused in high-temperature environments.
Smart Images

Figure CN119604595A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a pressure-sensitive adhesive sheet and an optical laminate. Background Art
[0002] Various image display devices represented by liquid crystal display devices and electroluminescent (EL) display devices generally have an optical laminate including an optical film such as a polarizing film and an adhesive sheet. Adhesive sheets are usually used to bond the optical films contained in the optical laminate and to bond the optical laminate to the image display panel. As an adhesive sheet, a typical sheet is obtained by curing a monomer group including an acrylic monomer, a silicone monomer, etc. by polymerization and crosslinking. An example of an adhesive sheet is disclosed in Patent Document 1.
[0003] For an image display device, static electricity is generated during its manufacture, for example, when an optical laminate is attached to an image display panel via an adhesive sheet, or during use, for example, when a user touches the image display device. Due to the static electricity, the image display device may be charged and display failure may occur. In order to prevent display failure caused by charging of the image display device, for example, a conductive layer, particularly a conductive layer containing a metal oxide such as ITO (indium tin oxide), is sometimes configured on the surface of the image display panel.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent No. 3052972 Summary of the invention
[0007] Problems to be solved by the invention
[0008] If the adhesive sheet is in contact with a conductive layer disposed on the surface of the image display panel, particularly a conductive layer containing metal oxides such as ITO, there is a tendency for the conductive layer to corrode according to the composition of the adhesive sheet. The adhesive sheet formed by the adhesive composition having a small amount of carboxyl-containing monomers in the monomer group has a tendency to suppress the corrosion of the conductive layer. However, according to the research of the inventors, if the amount of carboxyl-containing monomers is small, the anchoring force between the adhesive sheet and the optical film is reduced, and it is easy to peel off between the adhesive sheet and the optical film. This problem occurs particularly significantly when the adhesive sheet is made by a photocuring method, when it is repeatedly used in a high temperature environment, when the optical film includes a uniaxially stretched film such as a polarizer, and when the thickness of the adhesive sheet is less than 30 μm.
[0009] Therefore, the present invention provides a pressure-sensitive adhesive sheet that can suppress corrosion of a conductive layer, particularly a conductive layer made of a metal oxide such as ITO, and is suitable for adjusting the anchoring force with an optical film to a large value.
[0010] Solutions to the problem
[0011] The present invention provides an adhesive sheet, which is formed from an adhesive composition containing a monomer group and / or a polymer of the monomer group.
[0012] The adhesive sheet has a first surface and a second surface facing each other.
[0013] The pressure-sensitive adhesive sheet satisfies at least one selected from the following requirements (1) and (2).
[0014] (1) In 100 parts by weight of the above monomer group, the amount of the carboxyl group-containing monomer is 0.5 parts by weight or less,
[0015] When the first surface is treated with trifluoroethanol, an element ratio R1 of fluorine on the first surface is 0.1 atomic % or more.
[0016] (2) The adhesive composition contains an anticorrosive agent,
[0017] In 100 parts by weight of the above monomer group, the amount of the carboxyl group-containing monomer is 7.0 parts by weight or less.
[0018] When the first surface is treated with trifluoroethanol, an element ratio R1 of fluorine on the first surface is 0.1 atomic % or more.
[0019] Furthermore, the present invention provides an optical layered body comprising:
[0020] The above adhesive sheet, and
[0021] An optical film including at least one selected from a polarizing film and a retardation film.
[0022] Furthermore, the present invention provides an optical layered body comprising:
[0023] The above adhesive sheet, and
[0024] A conductive layer comprising a metal oxide.
[0025] Effects of the Invention
[0026] According to the present invention, it is possible to provide a pressure-sensitive adhesive sheet that can suppress corrosion of a conductive layer, particularly a conductive layer made of a metal oxide such as ITO, and is suitable for adjusting the anchoring force with an optical film to a large value. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a cross-sectional view schematically showing an example of the pressure-sensitive adhesive sheet of the present invention.
[0028] Figure 2A This is a schematic diagram for explaining a method for measuring the creep amount of a PSA sheet.
[0029] Figure 2B This is a schematic diagram for explaining a method for measuring the creep amount of a PSA sheet.
[0030] Figure 3A This is a schematic diagram for explaining an example of the method for producing the pressure-sensitive adhesive sheet of the present invention.
[0031] Figure 3B This is a schematic diagram for explaining an example of the method for producing the pressure-sensitive adhesive sheet of the present invention.
[0032] Figure 3C This is a schematic diagram for explaining an example of the method for producing the pressure-sensitive adhesive sheet of the present invention.
[0033] Figure 4 This is a cross-sectional view schematically showing an example of the optical layered body of the present invention.
[0034] Figure 5 This is a cross-sectional view schematically showing an example of the optical layered body of the present invention.
[0035] Figure 6 This is a cross-sectional view schematically showing an example of the optical layered body of the present invention. DETAILED DESCRIPTION
[0036] The first aspect of the present invention is a pressure-sensitive adhesive sheet formed from a pressure-sensitive adhesive composition containing a monomer group and / or a polymer of the monomer group.
[0037] The adhesive sheet has a first surface and a second surface facing each other.
[0038] The adhesive sheet satisfies at least one of the following requirements (1) and (2):
[0039] (1) In 100 parts by weight of the above monomer group, the amount of the carboxyl group-containing monomer is 0.5 parts by weight or less,
[0040] When the first surface is treated with trifluoroethanol, an element ratio R1 of fluorine on the first surface is 0.1 atomic % or more.
[0041] (2) The adhesive composition contains an anticorrosive agent,
[0042] In 100 parts by weight of the above monomer group, the amount of the carboxyl group-containing monomer is 7.0 parts by weight or less.
[0043] When the first surface is treated with trifluoroethanol, an element ratio R1 of fluorine on the first surface is 0.1 atomic % or more.
[0044] In the second aspect of the present invention, for example, in the pressure-sensitive adhesive sheet of the first aspect, when the second surface is treated with trifluoroethanol, an element ratio R2 of fluorine on the second surface is less than 0.1 atomic %.
[0045] In a third aspect of the present invention, for example, in the pressure-sensitive adhesive sheet of the first or second aspect, the pressure-sensitive adhesive composition is a photocurable pressure-sensitive adhesive composition.
[0046] In a fourth aspect of the present invention, for example, in the PSA sheet according to any one of the first to third aspects, the PSA composition has a solvent content of 5% by weight or less.
[0047] In a fifth aspect of the present invention, for example, in the pressure-sensitive adhesive sheet according to any one of the first to fourth aspects, the first surface is a surface subjected to a surface modification treatment.
[0048] In a sixth aspect of the present invention, for example, in the pressure-sensitive adhesive sheet of the fifth aspect, the surface modification treatment is a corona treatment.
[0049] In a seventh aspect of the present invention, for example, in the adhesive sheet of any one of the first to sixth aspects, the corrosion inhibitor includes at least one selected from silicon-containing compounds having an acidic group or an acid anhydride group, phosphoric acid compounds, and phosphonic acid compounds.
[0050] In an eighth aspect of the present invention, for example, in the pressure-sensitive adhesive sheet according to any one of the first to seventh aspects, the monomer group includes a (meth)acrylic monomer.
[0051] In a ninth aspect of the present invention, for example, the thickness of the pressure-sensitive adhesive sheet according to any one of the first to eighth aspects is 50 μm or less.
[0052] The optical layered body according to the tenth aspect of the present invention includes:
[0053] The pressure-sensitive adhesive sheet according to any one of the first to ninth aspects, and
[0054] An optical film including at least one selected from a polarizing film and a retardation film.
[0055] In the 11th aspect of the present invention, for example, in the optical layered body of the tenth aspect, the first surface of the pressure-sensitive adhesive sheet is in contact with the optical film.
[0056] In a twelfth aspect of the present invention, for example, in the optical laminate of the tenth or eleventh aspect, an anchoring force between the pressure-sensitive adhesive sheet and the optical film is 10.0 N / 25 mm or more.
[0057] The optical layered body according to the thirteenth aspect of the present invention includes:
[0058] The pressure-sensitive adhesive sheet according to any one of the first to ninth aspects, and
[0059] A conductive layer comprising a metal oxide.
[0060] In a fourteenth aspect of the present invention, for example, in the optical laminate according to the thirteenth aspect, the second surface of the pressure-sensitive adhesive sheet is in contact with the conductive layer.
[0061] Hereinafter, the present invention will be described in detail, but the present invention is not limited to the following embodiments and can be implemented with arbitrary modifications within the scope not departing from the gist of the present invention.
[0062] [Embodiments of Pressure-Sensitive Adhesive Sheet]
[0063] An example of the pressure-sensitive adhesive sheet of this embodiment is shown in Figure 1 . Figure 1 The adhesive sheet 1 is formed of an adhesive composition containing a monomer group and / or a polymer of the monomer group. The adhesive sheet 1 has a first surface 1a and a second surface 1b facing each other. As an example, the adhesive sheet 1 is attached to the optical film via the first surface 1a, and the adhesive sheet 1 is attached to the conductive layer of the image display panel via the second surface 1b.
[0064] The pressure-sensitive adhesive sheet 1 satisfies at least one selected from the following requirements (1) and (2).
[0065] (1) The amount of the carboxyl group-containing monomer in 100 parts by weight of the monomer group is 0.5 parts by weight or less,
[0066] When the first surface 1 a of the pressure-sensitive adhesive sheet 1 is treated with trifluoroethanol, the element ratio R1 of fluorine on the first surface 1 a is 0.1 atomic % or more.
[0067] (2) the adhesive composition comprises an anticorrosive agent,
[0068] The amount of the carboxyl group-containing monomer in 100 parts by weight of the monomer group is 7.0 parts by weight or less.
[0069] When the first surface 1 a of the pressure-sensitive adhesive sheet 1 is treated with trifluoroethanol, the element ratio R1 of fluorine on the first surface 1 a is 0.1 atomic % or more.
[0070] In the adhesive sheet 1 satisfying the requirement (1) or (2), the amount of the carboxyl group-containing monomer in the adhesive composition is sufficiently small, and there is a tendency that the corrosion of the conductive layer can be suppressed even when the adhesive sheet 1 (particularly the second surface 1b of the adhesive sheet 1) is in contact with the conductive layer. Furthermore, according to the first surface 1a having an element ratio R1 of 0.1 atomic % or more, there is a tendency that the anchoring force between the adhesive sheet 1 and the optical film can be adjusted to a larger value.
[0071] The above-mentioned element ratio R1 is preferably 0.2 atomic % or more, may be 0.3 atomic % or more, and may be 0.4 atomic % or more. The upper limit of the element ratio R1 is, for example, 1.0 atomic % or less.
[0072] The element ratio R1 can be determined by the following method. First, prepare an adhesive sheet 1 cut into 10 mm in length and 10 mm in width, and adhere the adhesive sheet 1 to the inner wall of the sample tube in such a way that the first surface 1a is exposed. Trifluoroethanol (TFE) is added to the sample tube, and the vaporized TFE is brought into contact with the adhesive sheet 1. Thus, the first surface 1a can be treated with TFE. According to the treatment with TFE, the carboxyl group present on the first surface 1a reacts with TFE, and the carboxyl group is chemically modified. The reaction of the carboxyl group with TFE is represented by the following formula. It should be noted that the amount of TFE added to the sample tube is adjusted in such a way that all the carboxyl groups present on the first surface 1a can react with TFE.
[0073] R-COOH+CF3CH2OH→R-COOCH2CF3
[0074] Next, the adhesive sheet 1 treated with TFE is taken out from the sample tube and placed in an X-ray photoelectron spectroscopy analyzer. The first surface 1a of the adhesive sheet 1 is subjected to a wide scan measurement by the X-ray photoelectron spectroscopy analyzer for qualitative analysis. The elements present on the first surface 1a are thereby determined. Next, a narrow scan measurement is performed on each element present on the first surface 1a. Based on the results of the narrow scan measurement, the element ratio R1 of fluorine on the first surface 1a can be determined. It should be noted that, typically, the fluorine on the first surface 1a comes from TFE that has reacted with a carboxyl group. Therefore, the element ratio R1 can be used as an indicator of the amount of carboxyl groups present on the first surface 1a before treatment with TFE.
[0075] In the present embodiment, when the second surface 1b of the adhesive sheet 1 is treated with TFE, the element ratio R2 of fluorine in the second surface 1b is, for example, different from the element ratio R1, and is preferably less than 0.1 atom%. When the element ratio R2 is less than 0.1 atom%, there is a tendency to further suppress the corrosion of the conductive layer. In particular, when the adhesive sheet 1 does not contain an anticorrosive agent, the element ratio R2 is preferably less than 0.08 atom%, more preferably less than 0.05 atom%, and further preferably less than 0.03 atom%. However, it should be noted that the element ratio R2 can also be the same value as the element ratio R1. In particular, when the adhesive sheet 1 contains an anticorrosive agent, the element ratio R2 can satisfy the range described above for the element ratio R1.
[0076] The element ratio R2 can be measured in the same manner as the element ratio R1, except that the adhesive sheet 1 is attached to the inner wall of the sample tube so that the second surface 1b is exposed, the second surface 1b is treated with TFE, and the second surface 1b is subjected to elemental analysis by an X-ray photoelectron spectrometer.
[0077] The first surface 1a of the adhesive sheet 1 is preferably a surface to which a surface modification treatment is applied. According to the research of the inventors, by applying a surface modification treatment to the first surface 1a, the above-mentioned element ratio R1 increases, and there is a tendency to improve the anchoring force between the adhesive sheet 1 and the optical film. On the other hand, it is preferred that the second surface 1b of the adhesive sheet 1 is not subjected to a surface modification treatment. As surface modification treatments, corona treatment, plasma treatment, excimer treatment, flame treatment, etc. can be cited. The first surface 1a is preferably subjected to a corona treatment as a surface modification treatment.
[0078] The surface modification treatment may be implemented in an inert gas atmosphere. By performing the surface modification treatment in a state where the oxygen concentration is reduced by using an inert gas, the risk of ignition of the residual monomer can be reduced. Specifically, the surface modification treatment is preferably performed at an oxygen concentration of 8% by volume or less, more preferably 6% by volume or less, and further preferably 3% by volume or less. If the oxygen concentration is too low, it may cause the introduction of functional groups to the surface of the adhesive sheet by the surface modification treatment to become insufficient, and therefore, the oxygen concentration is preferably 0.01% by volume or more, more preferably 0.1% by volume or more, and particularly preferably 0.5% by volume or more. As specific examples of inert gases, nitrogen and argon can be cited. The surface modification treatment can be implemented at normal pressure (1 atmosphere).
[0079] The conditions of the surface modification treatment as the corona treatment are represented by the discharge amount, for example, 0.6 to 100 kJ / m 2 The lower limit of discharge can be 1kJ / m 2 Above, 2kJ / m 2 Above, 5kJ / m 2 Above, 7kJ / m 2 Above, 10kJ / m 2 Above, 13kJ / m 2 Above, 15kJ / m 2 Above, 20kJ / m 2 Above, 25kJ / m 2 Above, 30kJ / m 2 Above, it can be 35kJ / m 2 The upper limit of the discharge amount can be 70 kJ / m 2 Below, 60kJ / m 2 Below, 50kJ / m 2 Below, 45kJ / m2 Below, 40kJ / m 2 Below, 30kJ / m 2 Below, 20kJ / m 2 Below, and further can be 18kJ / m 2 When the corona treatment is performed in an atmosphere with an oxygen concentration of 10 volume % or more and 20.9 volume % or less, the discharge amount can be 1 to 18 kJ / m 2 When the corona treatment is performed in an atmosphere having an oxygen concentration of 0.01 volume % or more and less than 10 volume %, the discharge amount may be 1 to 60 kJ / m 2 By appropriately adjusting the discharge amount of the corona treatment, there is a tendency for the anchoring force between the pressure-sensitive adhesive sheet 1 and the optical film to be further improved.
[0080] (Adhesive composition)
[0081] As described above, the adhesive sheet 1 is formed of an adhesive composition. The adhesive composition is preferably a photocurable adhesive composition that forms the adhesive sheet 1 by irradiation with light. However, it should be noted that the adhesive composition may also be a thermosetting adhesive composition that forms the adhesive sheet 1 by heat.
[0082] It should be noted that, in general, adhesive sheets can be manufactured by, for example, the following thermal curing method. First, a crosslinking agent is added to a polymer obtained by polymerizing a polymerizable monomer in an organic solvent to prepare an adhesive composition. The adhesive composition is applied to a substrate such as a release liner, and the organic solvent is heated and removed to form a sheet. Heating and aging are performed as required to complete crosslinking, thereby enabling the manufacture of an adhesive sheet. In this manufacturing process, in order to generate the heat energy required for heating and aging of the solvent, it is necessary to burn a large amount of fuel such as LNG. In addition, if the organic solvent after heating and removal is directly discharged into the atmosphere, there is a hidden danger of causing serious adverse effects on the surrounding environment. Therefore, for organic solvents, in most cases, they are released after being burned in a deodorizing furnace, etc. In this case, not only does the fuel used for burning in the deodorizing furnace become more necessary, but the organic solvent itself is also converted into CO2 and discharged into the atmosphere due to combustion, which is a manufacturing process with a very large CO2 emission.
[0083] In recent years, climate change caused by greenhouse gases is an urgent issue, and governments of various countries have proposed numerical targets and are committed to CO2 reduction. Therefore, in the manufacture of adhesive sheets, it is also preferred to select a manufacturing process that does not use organic solvents and has low CO2 emissions. Compared with the thermal curing method, the method of making an adhesive sheet using light (photocuring method) has a tendency to reduce the energy required for the formation of the adhesive sheet and the CO2 emissions.
[0084] According to the research of the inventors, in the past, when an adhesive sheet formed by a photocurable adhesive composition was used, there was a tendency for the adhesive sheet to be easily peeled off from the optical film compared to the case where an adhesive sheet formed by a thermosetting adhesive composition was used. It can be inferred that the reason for this tendency is that when an adhesive sheet formed by a thermosetting adhesive composition is bonded to an optical film, the curing of the adhesive sheet is further performed on the surface of the optical film, while on the other hand, the adhesive sheet formed by the photocurable adhesive composition is hardly cured after being bonded to the optical film. In this embodiment, by satisfying the above-mentioned requirements (1) or (2), there is a tendency that the peeling between the adhesive sheet 1 and the optical film can be fully suppressed even when the adhesive sheet 1 is formed by a photocurable adhesive composition.
[0085] As described above, the adhesive composition contains a monomer group and / or a polymer of the monomer group. The monomer group, for example, contains a (meth)acrylic monomer. The content of the (meth)acrylic component in the adhesive composition, i.e., the (meth)acrylic monomer and its polymer, can be 50% by weight or more, 60% by weight or more, 70% by weight or more, and further can be 80% by weight or more. In this case, an acrylic adhesive sheet 1 with (meth)acrylic polymer and its crosslinked product as the main component can be formed. However, the adhesive composition is not limited to the above examples. In this specification, (meth)acrylic acid refers to acrylic acid and methacrylic acid. (Meth)acrylate refers to acrylate and methacrylate. It should be noted that the monomer contained in the monomer group preferably does not contain fluorine atoms.
[0086] Examples of (meth)acrylic monomers include (meth)acrylic acid alkyl esters having an alkyl group having 1 to 20 carbon atoms in a side chain. The number of carbon atoms in the alkyl group may be 7 or less, 6 or less, 5 or less, or 4 or less. The alkyl group may be linear or branched. Examples of the alkyl (meth)acrylates are methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, isobutyl (meth)acrylate, n-pentyl (meth)acrylate, isopentyl (meth)acrylate, n-hexyl (meth)acrylate, isohexyl (meth)acrylate, isoheptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, n-nonyl (meth)acrylate, isononyl (meth)acrylate, n-decyl (meth)acrylate, isodecyl (meth)acrylate, n-dodecyl (meth)acrylate (lauryl (meth)acrylate), n-tridecyl (meth)acrylate, n-tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, and octadecyl (meth)acrylate. The alkyl (meth)acrylate may be n-butyl (meth)acrylate.
[0087] The amount of the (meth)acrylic acid alkyl ester in 100 parts by weight of the monomer group is, for example, 40 parts by weight or more, and may be 50 parts by weight or more, 60 parts by weight or more, 70 parts by weight or more, 80 parts by weight or more, 85 parts by weight or more, 90 parts by weight or more, and may be 95 parts by weight or more. It should be noted that when calculating the amount of a specific monomer, the weight of the polymer is converted into the weight of each monomer before polymerization.
[0088] The monomer group may include a carboxyl-containing monomer. The carboxyl-containing monomer may be a (meth)acrylic monomer, in other words, the (meth)acrylic monomer may include a carboxyl-containing monomer. Examples of carboxyl-containing monomers are (meth)acrylic acid, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, itaconic acid, maleic acid, fumaric acid, and crotonic acid.
[0089] As mentioned above, the amount of the carboxyl-containing monomer in 100 weight parts of monomer group is preferably below 0.5 weight part, can be below 0.4 weight part, below 0.3 weight part, below 0.2 weight part, and then can be below 0.1 weight part.Monomer group also can not comprise carboxyl-containing monomer.If the amount of the carboxyl-containing monomer is below 0.5 weight part, then there is the tendency that can fully suppress the corrosion of conductive layer even when the adhesive composition does not comprise anticorrosive.
[0090] In the case where the adhesive composition includes an anticorrosive, the amount of the carboxyl-containing monomer in 100 parts by weight of the monomer group can be higher than 0.5 parts by weight. In this case, the amount of the carboxyl-containing monomer is less than 7.0 parts by weight, and can be less than 5.0 parts by weight, less than 4.0 parts by weight, less than 3.5 parts by weight, less than 3.0 parts by weight, less than 2.5 parts by weight, less than 2.0 parts by weight, less than 1.5 parts by weight, and then can be less than 1.0 parts by weight. Carboxyl-containing monomers are preferably combined in large quantities as long as they are within the range that can suppress corrosion. In the case where the amount of carboxyl-containing monomers is large, there is a tendency that the anchoring force of the adhesive sheet 1 and the optical film is improved. In this case, when the adhesive sheet 1 is made by a photocuring method, there is also a tendency that the polymerization rate of the monomer group based on the illumination becomes faster, and productivity is improved, so it is preferred.
[0091] The monomer group may include a hydroxyl-containing monomer. The hydroxyl-containing monomer may be a (meth) acrylic monomer, in other words, the (meth) acrylic monomer may include a hydroxyl-containing monomer. The hydroxyl-containing monomer may contribute to the improvement of the cohesive force of the adhesive sheet. Examples of hydroxyl-containing monomers are 2-hydroxyethyl (meth) acrylate, 2-hydroxypropyl (meth) acrylate, 4-hydroxybutyl (meth) acrylate, 6-hydroxyhexyl (meth) acrylate, 8-hydroxyoctyl (meth) acrylate, 10-hydroxydecyl (meth) acrylate, 12-hydroxylauryl (meth) acrylate, and methyl acrylate (4-hydroxymethylcyclohexyl). The hydroxyl-containing monomer is preferably 2-hydroxyethyl (meth) acrylate and 4-hydroxybutyl (meth) acrylate. The amount of the hydroxyl-containing monomer in 100 parts by weight of the monomer group is, for example, less than 20 parts by weight, and may be less than 15 parts by weight, less than 10 parts by weight, less than 7.5 parts by weight, less than 5 parts by weight, less than 4 parts by weight, less than 3 parts by weight, less than 2 parts by weight, less than 1 part by weight, and further may be less than 0.5 parts by weight. The lower limit of the amount of the compounding agent is, for example, 0.01 parts by weight or more, 0.03 parts by weight or more, or 0.05 parts by weight or more. The monomer group may not contain a hydroxyl group-containing monomer.
[0092] The monomer group may include an ether group-containing monomer. The ether group-containing monomer may be a (meth)acrylic monomer, in other words, the (meth)acrylic monomer may include an ether group-containing monomer. The ether group-containing monomer may contribute to improving the anchoring force between the adhesive sheet 1 and the optical film.
[0093] The ether group-containing monomer is preferably an alkoxy group-containing monomer. Examples of the alkoxy group-containing monomer include alkylene oxide adducts represented by the following chemical formula (1). 1 is a hydrogen atom or a methyl group. 2 is an alkyl group. The alkyl group may be linear or branched. 2 Preferably, it is a straight-chain alkyl group. 2Examples of the group are methyl and ethyl. n in formula (1) is an integer of 1 to 30, preferably an integer of 1 to 12, and may be an integer of 1 to 5.
[0094] [Chemical formula 1]
[0095]
[0096] Examples of the alkylene oxide adduct represented by formula (1) are 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 2-(2-ethoxyethoxy)ethyl (meth)acrylate, methoxytriethylene glycol (meth)acrylate, and methoxypolyethylene glycol (meth)acrylate, preferably 2-methoxyethyl acrylate (MEA).
[0097] The ether group-containing monomer is not limited to the above-mentioned alkylene oxide adduct. The ether group-containing monomer may have a ring structure, and the ring structure may have an ether group. Examples of the ring structure having an ether group include tetrahydrofuran ring, dihydrofuran ring, Alkane ring, etc. Examples of the ether group-containing monomer having a ring structure are cyclic trimethylolpropane formal (meth)acrylate and tetrahydrofurfuryl (meth)acrylate.
[0098] The amount of the ether group-containing monomer in 100 parts by weight of the monomer group is, for example, 1 part by weight or more, 5 parts by weight or more, 10 parts by weight or more, 20 parts by weight or more, 25 parts by weight or more, 30 parts by weight or more, 40 parts by weight or more, 50 parts by weight or more, 60 parts by weight or more, 70 parts by weight or more, 80 parts by weight or more, and further 90 parts by weight or more. The upper limit of the amount is, for example, 99 parts by weight or less, and may be 50 parts by weight or less depending on the circumstances. The monomer group may not contain the ether group-containing monomer.
[0099] In the adhesive composition, each monomer mentioned above can be included in the form of a polymer. When the adhesive composition is photocurable, the polymer is preferably a partial polymer. The partial polymer can be any polymer in a homopolymer and a copolymer. The partial polymer can be appropriately increased by the viscosity of the adhesive composition to contribute to the stable formation of the coating layer described later.
[0100] The adhesive composition may contain a photopolymerization initiator. Examples of the photopolymerization initiator include a photoradical generator that generates radicals by visible light and / or ultraviolet light having a wavelength shorter than 450 nm.
[0101] Examples of photopolymerization initiators include benzoin ethers such as benzoin methyl ether, benzoin isopropyl ether, and benzoin dimethyl ether; substituted benzoin ethers such as anisole methyl ether; substituted acetophenones such as 2,2-diethoxyacetophenone and 2,2-dimethoxy-2-phenylacetophenone; α-hydroxyalkyl phenones such as 1-hydroxycyclohexyl phenyl ketone; substituted α-ol ketones such as 2-methyl-2-hydroxypropiophenone; aromatic sulfonyl chlorides such as 2-naphthalenesulfonyl chloride; photoactive oximes such as 1-phenyl-1,1-propanedione-2-(o-ethoxycarbonyl)-oxime; benzophenone, benzoylbenzoic acid, benzoylbenzoic acid, Benzophenone compounds such as methyl benzoate, 4-phenylbenzophenone, hydroxybenzophenone, acryloyl benzophenone, 4-benzoyl-4'-methyldiphenyl sulfide, 3,3',4,4'-tetra(tert-butylperoxycarbonyl)benzophenone; thioxanthone compounds such as thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, isopropylthioxanthone, 2,4-diisopropylthioxanthone, 2,4-diethylthioxanthone; 2,4,6-trichloro-s-triazine, 2-phenyl-4,6-bis(trichloromethyl)-s-triazine, 2-(p-methoxyphenyl)-4,6 -bis(trichloromethyl)-s-triazine, 2-(p-tolyl)-4,6-bis(trichloromethyl)-s-triazine, 2-piperonyl-4,6-bis(trichloromethyl)-s-triazine, 2,4-bis(trichloromethyl)-6-phenylvinyl-s-triazine, 2-(naphthalene-1-yl)-4,6-bis(trichloromethyl)-s-triazine, 2-(4-methoxy-naphthalene-1-yl)-4,6-bis(trichloromethyl)-s-triazine, 2,4-trichloromethyl-(piperonyl)-6-triazine, 2,4-trichloromethyl-(4'-methoxyphenylvinyl)-6-triazine, etc. Oxime ester compounds such as 1,2-octanedione, 1-[4-(phenylthio)-, 2-(O-benzoyloxime)], O-(acetyl)-N-(1-phenyl-2-oxo-2-(4'-methoxy-naphthyl)ethylidene)hydroxylamine; phosphine compounds such as bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide and 2,4,6-trimethylbenzoyldiphenylphosphine oxide; quinone compounds such as 9,10-phenanthrenequinone, camphorquinone, and ethylanthraquinone; borate ester compounds; carbazole compounds; imidazole compounds; and titanocene compounds. The adhesive composition may contain one or more photopolymerization initiators.
[0102] The amount of the photopolymerization initiator in the adhesive composition may be, for example, 0.02 to 10 parts by weight, or 0.05 to 5 parts by weight, relative to 100 parts by weight of the total of the monomer group and the polymer thereof.
[0103] The adhesive composition may include a crosslinking agent. An example of a crosslinking agent is a multifunctional monomer having two or more polymerizable functional groups in one molecule. The multifunctional monomer may be a (meth)acrylic monomer. An example of a multifunctional monomer is a monomer having two or more C=C bonds in one molecule, and a monomer having one or more C=C bonds and one or more epoxy groups, aziridine groups, The polyfunctional monomer preferably has two or more C═C bonds in one molecule.
[0104] Examples of the multifunctional monomer include: multifunctional acrylates (ester compounds formed by polyols and (meth)acrylic acid, etc.) such as (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, 1,2-ethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol diacrylate (NDDA), 1,12-dodecanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, and tetramethylolmethane tri(meth)acrylate; allyl (meth)acrylate, vinyl (meth)acrylate, divinylbenzene, epoxy acrylate, polyester acrylate, urethane acrylate, butyl di(meth)acrylate, and hexyl di(meth)acrylate. The polyfunctional monomer is preferably a polyfunctional acrylate, and more preferably trimethylolpropane tri(meth)acrylate, hexanediol di(meth)acrylate, or dipentaerythritol hexa(meth)acrylate.
[0105] The crosslinking agent may also include other crosslinking agents other than the above-mentioned multifunctional monomer. As other crosslinking agents, isocyanate crosslinking agents may be cited. The adhesive composition may include an isocyanate crosslinking agent as a crosslinking agent, and may also include both the above-mentioned multifunctional monomer and the isocyanate crosslinking agent. The isocyanate crosslinking agent may contribute to the improvement of the anchoring force between the adhesive sheet 1 and the optical film.
[0106] As an isocyanate crosslinking agent, a compound having at least two isocyanate groups (isocyanate compound) can be used. The number of isocyanate groups contained in the isocyanate compound is preferably 3 or more. The upper limit of the number of isocyanate groups is not particularly limited, for example, 5. As the isocyanate compound, aromatic isocyanate compounds, alicyclic isocyanate compounds, aliphatic isocyanate compounds, etc. can be cited.
[0107] Examples of the aromatic isocyanate compound include phenylene diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 2,2′-diphenylmethane diisocyanate, 4,4′-diphenylmethane diisocyanate, 4,4′-toluidine diisocyanate, 4,4′-diphenyl ether diisocyanate, 4,4′-diphenyl diisocyanate, 1,5-naphthalene diisocyanate, and xylylene diisocyanate.
[0108] Examples of the alicyclic isocyanate compound include 1,3-cyclopentene diisocyanate, 1,3-cyclohexane diisocyanate, 1,4-cyclohexane diisocyanate, isophorone diisocyanate, hydrogenated diphenylmethane diisocyanate, hydrogenated xylylene diisocyanate, hydrogenated toluene diisocyanate, and hydrogenated tetramethylxylylene diisocyanate.
[0109] Examples of the aliphatic isocyanate compound include trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate (HDI), pentamethylene diisocyanate (PDI), 1,2-propylene diisocyanate, 1,3-butylene diisocyanate, dodecamethylene diisocyanate, and 2,4,4-trimethylhexamethylene diisocyanate.
[0110] As isocyanate crosslinking agents, there can also be mentioned polymers (dimers, trimers, pentamers, etc.) of the above-mentioned isocyanate compounds, adducts obtained by addition of polyols such as trimethylolpropane, urea-modified products, biuret-modified products, allophanate-modified products, isocyanurate-modified products, carbodiimide-modified products, and urethane prepolymers obtained by addition of polyether polyols, polyester polyols, acrylic polyols, polybutadiene polyols, polyisoprene polyols, etc.
[0111] The isocyanate crosslinking agent preferably comprises an aliphatic isocyanate compound and / or a derivative of an aliphatic isocyanate compound. The isocyanate crosslinking agent is particularly preferably at least one selected from pentamethylene diisocyanate (PDI) crosslinking agents (PDI and its derivatives) and hexamethylene diisocyanate (HDI) crosslinking agents (HDI and its derivatives). Specific examples of PDI crosslinking agents include isocyanurate modified products of PDI, etc. Specific examples of HDI crosslinking agents include isocyanurate modified products of HDI, biuret modified products, etc.
[0112] The amount of the crosslinking agent in the adhesive composition varies depending on the molecular weight, the number of functional groups, etc., and is, for example, 5 parts by weight or less, 3 parts by weight or less, 2 parts by weight or less, 1 part by weight or less, and further 0.5 parts by weight or less, relative to 100 parts by weight of the total of the monomer group and the polymer thereof. The lower limit of the amount of the crosslinking agent is, for example, 0.01 parts by weight or more, and further 0.05 parts by weight or more.
[0113] It should be noted that, when the adhesive composition includes an isocyanate crosslinking agent, the amount of the isocyanate crosslinking agent is, for example, 0.02 parts by weight or more, 0.05 parts by weight or more, 0.1 parts by weight or more, 0.5 parts by weight or more, and further 1 part by weight or more relative to a total of 100 parts by weight of the monomer group and its polymer. When the adhesive composition includes an isocyanate crosslinking agent, if the amount of the hydroxyl-containing monomer in the adhesive composition is adjusted to a smaller value, there is a tendency that the anchoring force between the adhesive sheet 1 and the optical film is further improved.
[0114] When an isocyanate crosslinking agent is added, the adhesive sheet sometimes hardens, especially in a high temperature environment. In such a case, the stress relaxation of the adhesive sheet is impaired, and therefore, there is a tendency that the expansion and contraction stress of the optical film is easily transmitted to the interface between the adhesive sheet and the adherend, and peeling is easily caused. In the case where the anchoring force between the adhesive sheet and the optical film can be ensured by a method other than adding an isocyanate crosslinking agent, it is preferred that the adhesive composition does not contain an isocyanate crosslinking agent.
[0115] Adhesive composition can include anticorrosive. Anticorrosive, for example, when adhesive sheet 1 is pasted to conductive layers such as ITO layers, can segregate on the surface of the conductive layer to form a coating layer covering the surface of the conductive layer. Through the coating layer, it is possible to suppress the corrosive substances (for example, acid components) contained in the adhesive sheet 1 from moving to the conductive layer. According to the coating layer, by reducing the adhesive force of the adhesive sheet 1 and the conductive layer, there is also a tendency to improve the reoperability of the adhesive sheet 1.
[0116] The anticorrosive agent, for example, includes at least one selected from silicon-containing compounds having acidic groups or acid anhydride groups, phosphoric acid compounds, and phosphonic acid compounds, and preferably includes silicon-containing compounds having acidic groups or acid anhydride groups.
[0117] As the silicon-containing compound, alkoxysilane compounds, organopolysiloxane compounds, etc. can be mentioned. In the silicon-containing compound, the acidic group is typically a carboxyl group. The carboxyl group can be a group generated by hydrolyzing anhydride groups. As the anhydride group, for example, carboxylic anhydride groups such as succinic anhydride groups, phthalic anhydride groups, and maleic anhydride groups can be mentioned. The silicon-containing compound preferably does not have a polyether skeleton.
[0118] The silicon-containing compound may be a silane coupling agent having an alkoxysilyl group. Specific examples of the alkoxy group contained in the alkoxysilyl group include a methoxy group and an ethoxy group.
[0119] Examples of the alkoxysilane compound having an acid anhydride group include 2-trimethoxysilylethylsuccinic anhydride, 3-trimethoxysilylpropylsuccinic anhydride (manufactured by Shin-Etsu Chemical Co., Ltd., trade name "X-12-967C"), 3-triethoxysilylpropylsuccinic anhydride, 3-methyldiethoxysilylpropylsuccinic anhydride, and 1-carboxy-3-triethoxysilylpropylsuccinic anhydride.
[0120] Examples of the organopolysiloxane compound having an acid anhydride group include an acid anhydride group-containing oligomer type silane coupling agent manufactured by Shin-Etsu Chemical Co., Ltd. (trade name: "X-24-9591F") and the like.
[0121] Examples of phosphoric acid compounds include phosphoric acid itself, phosphoric acid esters, and salts thereof. The phosphoric acid esters may be phosphoric acid monoesters or phosphoric acid diesters. The phosphoric acid esters, for example, have a structure in which a hydrocarbon group having 1 to 18 carbon atoms is introduced into phosphoric acid.
[0122] Examples of the phosphonic acid compounds include phosphonic acid itself, alkylphosphonic acid, and salts thereof. The alkyl group contained in the alkylphosphonic acid has, for example, 1 to 18 carbon atoms.
[0123] The amount of the anticorrosive agent in the adhesive composition is, for example, 0.01 parts by weight or more, 0.05 parts by weight or more, 0.1 parts by weight or more, 0.2 parts by weight or more, and further 0.4 parts by weight or more relative to a total of 100 parts by weight of the monomer group and its polymer. The upper limit of the amount is, for example, 10 parts by weight or less, 5 parts by weight or less, and further 1 part by weight or less. The adhesive composition may also not contain an anticorrosive agent.
[0124] The adhesive composition may contain additives other than those mentioned above. Examples of additives include silane coupling agents, viscosity modifiers, tackifiers, plasticizers, softeners, antioxidants, fillers, colorants, antioxidants, surfactants, antistatic agents, and ultraviolet absorbers, except for chain transfer agents and anticorrosive agents.
[0125] The content of the solvent in the adhesive composition is, for example, 5% by weight or less, 4% by weight or less, 3% by weight or less, 2% by weight or less, 1% by weight or less, and further 0.5% by weight or less. The adhesive composition may contain substantially no solvent. Substantially containing no solvent means that a solvent derived from an additive or the like is allowed to be contained at a content of, for example, 0.1% by weight or less, preferably 0.05% by weight or less, and more preferably 0.01% by weight or less.
[0126] The viscosity of the adhesive composition is preferably 5 to 150 poise. An adhesive composition having a viscosity within the above range is particularly suitable for forming a coating layer described below.
[0127] (Physical properties and characteristics of adhesive sheets)
[0128] The polymerization rate of the monomer group in the pressure-sensitive adhesive sheet 1 is preferably 90% or more. The polymerization rate may be 95% or more, 98% or more, or even 99% or more.
[0129] The gel fraction of the pressure-sensitive adhesive sheet 1 may be, for example, 50% or more, 75% or more, 80% or more, or even 85% or more.
[0130] The creep amount of the adhesive sheet 1 is, for example, 500 μm or less, 300 μm or less, 180 μm or less, 160 μm or less, 150 μm or less, 100 μm or less, or 50 μm or less. The lower limit of the creep amount is, for example, 5 μm or more, 10 μm or more, or 20 μm or more.
[0131] The creep amount of the adhesive sheet 1 can be evaluated as follows (see Figure 2A and Figure 2B ). First, a laminate of the adhesive sheet 1 and the support film 51 to be evaluated is cut into a 10 mm × 50 mm strip to prepare a test piece 52. The support film 51 is arranged for the purpose of suppressing the deformation of the load-applying portion of the adhesive sheet 1 to which a load is applied during the test, thereby measuring the creep amount with higher accuracy. The support film 51 can use a resin film such as a polyethylene terephthalate (PET) film. The support film 51 can be an optical film or a laminate including an optical film. The thickness of the support film 51 can be a thickness that does not deform due to the above-mentioned load, for example, 20 to 200 μm. Next, as Figure 2A and Figure 2B As shown, the test piece 52 is attached to the surface of the stainless steel test plate 53 by using the adhesive sheet 1 with a bonding surface of 10 mm in length and 10 mm in width. Figure 2B yes Figure 2A Section BB. The test piece 52 is pasted to the test plate 53 in a manner that does not allow bubbles to be mixed between the test plate 53 and the adhesive sheet 1. In addition, after pasting, it is placed in an autoclave at 50°C and 5 atmospheres (absolute pressure) for 15 minutes to homogenize the bonding between the test plate 53 and the adhesive sheet 1. Next, the test plate 53 and the test piece 52 are vertically held in an atmosphere of 25°C in such a manner that the test plate 53 is on top and are placed for at least 5 minutes. With the test plate 53 fixed, a weight of 500g is fixed at the center of the lower end of the test piece 52, and a load 54 of 500gf is applied vertically downward. The creep amount (displacement amount) of the adhesive sheet 1 relative to the test plate 53 at the moment 3600 seconds after the start of the application of the load 54 is measured as the amount of weight dropped. The amount of weight dropped can be measured using a laser displacement meter.
[0132] The thickness of the adhesive sheet 1 is, for example, 500 μm or less, 250 μm or less, 150 μm or less, 100 μm or less, 50 μm or less, 30 μm or less, 25 μm or less, or 20 μm or less. The lower limit of the thickness of the adhesive sheet 1 is, for example, 2 μm or more, and 5 μm or more.
[0133] (Method for producing adhesive sheet)
[0134] The method for producing the adhesive sheet 1 is not particularly limited. As an example, when the adhesive composition is photocurable, the adhesive sheet 1 can be produced by the following method. Figure 3A , Figure 3B As shown in FIG. 1 , a first laminate 15 is prepared which includes a substrate sheet 21, a coating layer 22 containing an adhesive composition, and a release liner 23 in this order. By irradiating the first laminate 15 with light 14, an adhesive sheet 1 ( Figure 3C ).
[0135] Typically, the irradiation of the first stacked body 15 with the light 14 can be carried out from one side of the base sheet 21 ( Figure 3A At this time, the light 14 passes through the substrate sheet 21 and reaches the coating layer 22, thereby curing the coating layer 22. However, it should be noted that the irradiation of the light 14 can be implemented from one side of the release liner 23, or from both sides of the release liner 23 and the substrate sheet 21 ( Figure 3B The pressure-sensitive adhesive sheet 1 formed of the coating layer 22 is sandwiched between the base sheet 21 and the release liner 23 to constitute a part of the second laminate 16 until the release liner 23 is peeled off.
[0136] An example of the base material of the release liner 23 (hereinafter referred to as "base material") is a resin film. Examples of the resin that can be contained in the base material are polyesters such as polyethylene terephthalate and polyethylene naphthalate, acetate resins, polyether sulfone, polycarbonate, polyamide, polyimide, polyolefin, (meth) acrylic resin, polyvinyl chloride, polyvinylidene chloride, polystyrene, polyvinyl alcohol, polyarylate, and polyphenylene sulfide. The resin is preferably a polyester such as polyethylene terephthalate.
[0137] The release liner 23 may have the transmittance of the light 14 or may have the same degree of transmittance of the light 14 as the base sheet 21 .
[0138] The thickness of the release liner 23 is, for example, 10 to 200 μm, or 25 to 150 μm.
[0139] The release liner 23 may include a layer other than the lining substrate. The release liner 23 may include a release layer. The release liner 23 may include, for example, a lining substrate and a release layer formed on one side of the lining substrate. The release liner 23 may be used in a manner such that the release layer is on the coating layer 22 side.
[0140] Typically, the release layer is a cured layer of a release agent composition containing a release agent. The release agent can use various release agents such as silicone release agents, fluorine release agents, long-chain alkyl release agents, fatty acid amide release agents, and silica powder. The release liner 23 can have a cured layer of a release agent composition containing a silicone release agent as a main component (hereinafter, "silicone release layer"). The silicone release layer is particularly suitable for balancing the adhesion and releasability relative to the adhesive sheet 1. It should be noted that in this specification, the main component refers to the component with the largest content.
[0141] The silicone release agent includes various curable silicone materials such as addition reaction type, condensation reaction type, ultraviolet curing type, electron beam curing type, solvent-free type, etc., preferably addition reaction curing type silicone materials. Addition reaction curing type silicone materials are particularly suitable for forming a release layer that takes into account both adhesion and peelability with respect to the adhesive sheet 1. The curable silicone material can be a silicone modified resin obtained by introducing reactive silicone into an organic resin such as urethane, epoxy, alkyd resin, etc. by graft polymerization.
[0142] Examples of addition reaction curing silicone materials are polyorganosiloxanes having vinyl or alkenyl groups in the molecule. Addition reaction curing silicone materials may not have hydrosilyl groups. Examples of alkenyl groups are 3-butenyl, 4-pentenyl, 5-hexenyl, 6-heptenyl, 7-octenyl, 8-nonenyl, 9-decenyl, 10-undecenyl and 11-dodecenyl. Examples of polyorganosiloxanes are copolymers of polyalkylalkylsiloxanes such as polydimethylsiloxane, polydiethylsiloxane and polymethylethylsiloxane, polyalkylarylsiloxane, and poly(dimethylsiloxane-diethylsiloxane) and other monomers containing Si atoms. Polyorganosiloxane is preferably polydimethylsiloxane.
[0143] A mold release composition containing a silicone-based mold release agent as a main component (hereinafter, "silicone mold release composition") generally contains a crosslinking agent. An example of the crosslinking agent is a polyorganosiloxane having a hydrosilyl group. The crosslinking agent may have two or more hydrosilyl groups in one molecule.
[0144] The silicone release agent composition may also contain a curing catalyst. Examples of the curing catalyst are platinum catalysts. Examples of platinum catalysts are chloroplatinic acid, olefin complexes of platinum, and olefin complexes of chloroplatinic acid. The amount of the platinum catalyst used is, for example, 10 to 1000 ppm (weight basis, converted to platinum) relative to the total solid content of the composition.
[0145] The silicone release agent composition may also contain additives. Examples of additives are release control agents and adhesion improvers. Examples of release control agents are unreactive silicone resins, and more specifically, organosiloxanes such as octamethylcyclotetrasiloxane and MQ resins. The total amount of release control agents and adhesion improvers is, for example, 1 to 30% by weight relative to the total solid content of the composition. Other examples of additives are fillers, antistatic agents, antioxidants, ultraviolet absorbers, plasticizers, and colorants. The total amount of other additives is, for example, 10% by weight or less relative to the total solid content of the composition.
[0146] The silicone release agent composition may also contain an organic solvent. Examples of organic solvents are hydrocarbon solvents such as cyclohexane, n-hexane, and n-heptane; aromatic solvents such as toluene and xylene; ester solvents such as ethyl acetate and methyl acetate; ketone solvents such as acetone and methyl ethyl ketone; and alcohol solvents such as methanol, ethanol, and butanol. Two or more organic solvents may also be contained. The amount of organic solvent used is preferably 80 to 99.9% by weight of the silicone release agent composition.
[0147] The release layer can be formed, for example, by heating and drying a coating film containing a release agent composition formed on a lining substrate. The release agent composition can be applied by various coating methods such as roller coating, roller lick coating, gravure coating, reverse coating, roller brush, spray coating, dip roller coating, rod coating, blade coating, air knife coating, shower coating, die lip coating, and die coating. Heating and drying can be performed by hot air drying, for example. The heating temperature and time vary depending on the heat resistance of the lining substrate, and are generally 80 to 150° C. and about 10 seconds to 10 minutes. As required, irradiation with active energy rays such as ultraviolet rays can also be used in combination.
[0148] The thickness of the release layer is, for example, 10 to 300 nm. The upper limit of the thickness may be 200 nm or less, 150 nm or less, 120 nm or less, 110 nm or less, 100 nm or less, less than 100 nm, 90 nm or less, 80 nm or less, 70 nm or less, less than 70 nm, and further may be 65 nm or less. The lower limit of the thickness may be 15 nm or more, 20 nm or more, 25 nm or more, 30 nm or more, 35 nm or more, 40 nm or more, 45 nm or more, and further may be 50 nm or more.
[0149] The release liner 23 may be in the form of a single sheet or in the form of a long strip.
[0150] An example of the base sheet 21 is a resin film. Examples of the resin contained in the base sheet 21 are the same as examples of the resin that can be contained in the backing base.
[0151] It is preferred that the base sheet 21 has excellent transmittance to the light 14 .
[0152] The thickness of the base sheet 21 is, for example, 10 to 200 μm, or 25 to 150 μm.
[0153] The substrate sheet 21 may have a release layer on the surface of the coating layer 22 side. The examples of the release layer and its preparation method that the substrate sheet 21 may have are the same as the examples of the release layer and its preparation method that the release liner 23 may have. It is also possible to have a release layer on both the release liner 23 and the substrate sheet 21. In this case, the release layers of the two may be formed by a release agent composition containing the same release agent as a main component. In addition, the thickness of the release layers of the two may be different, for example, the release layer of the substrate sheet 21 may be thicker.
[0154] The base sheet 21 can generally be selected to have a greater release force with the pressure-sensitive adhesive sheet 1 than the release liner 23 .
[0155] The base sheet 21 may be in a single sheet shape or in a long strip shape.
[0156] The first laminate 15 can be formed, for example, by forming a coating layer 22 on a substrate sheet 21 (or a release liner 23), and disposing a release liner 23 (or a substrate sheet 21) on the formed coating layer 22. Alternatively, the first laminate 15 can be formed by coating the adhesive composition so that it flows into a space between the substrate sheet 21 and the release liner 23, which are held at a predetermined interval so that their main surfaces face each other.
[0157] The coating layer 22 can be formed by various coating methods such as roll coating, lick roll coating, gravure coating, reverse coating, roller brushing, spray coating, dip roll coating, rod coating, blade coating, air knife coating, shower coating, die lip coating, and die coating.
[0158] The thickness of the coating layer 22 can be adjusted according to the target thickness of the adhesive sheet 1, and may be, for example, 5 to 500 μm, 5 to 250 μm, 5 to 150 μm, 5 to 100 μm, 5 to 50 μm, 5 to 30 μm, 5 to 25 μm, or even 5 to 20 μm.
[0159] The light 14 irradiated to the first stack 15 is, for example, visible light or ultraviolet light having a wavelength shorter than 450 nm. The light 14 may include light of a wavelength in the same region as the absorption wavelength of the photopolymerization initiator contained in the adhesive composition. The light 14 obtained by cutting off short-wavelength light with a wavelength of less than 300 nm through an optical filter or the like may be irradiated, and cutting off the short-wavelength light is suitable for suppressing the degradation of the substrate sheet 21 caused by the light 14. The light source of the light 14 is, for example, an irradiation device having an ultraviolet irradiation lamp. Examples of ultraviolet irradiation lamps are ultraviolet LEDs, low-pressure mercury lamps, medium-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, metal halide lamps, xenon lamps, microwave-excited mercury lamps, black light lamps, chemical lamps, sterilization lamps, low-pressure discharge mercury lamps, and excimer lasers. Two or more ultraviolet irradiation lamps may also be combined.
[0160] The irradiation of the light 14 may be continuous or intermittent.
[0161] The illuminance of the light 14 is, for example, 1 to 20 mW / cm 2 The irradiation time of the light 14 is, for example, 5 minutes to 5 hours. The cumulative light intensity of the light 14 on the first stack 15 is, for example, 100 to 5000 mJ / cm 2 .
[0162] If necessary, the release liner 23 may be peeled off from the second laminate 16 to expose the surface (eg, surface 1 a ) of the pressure-sensitive adhesive sheet 1 , and the surface may be subjected to a surface modification treatment.
[0163] [Embodiments of optical laminate]
[0164] An example of the optical layered body of the present embodiment is shown in Figure 4 . Figure 4 The optical laminate 10 comprises the above-mentioned adhesive sheet 1 and at least one optical film 2 selected from a polarizing film and a phase difference film. The adhesive sheet 1 is preferably directly in contact with the optical film 2. Figure 4 In the example, the first surface 1a of the pressure-sensitive adhesive sheet 1 is in contact with the optical film 2. The optical laminate 10 may have a structure in which a base sheet used when producing the pressure-sensitive adhesive sheet 1 is laminated on the pressure-sensitive adhesive sheet 1. The optical laminate 10 can be used as an optical film with a pressure-sensitive adhesive sheet.
[0165] (Optical Film)
[0166] The optical film 2 has a surface 2a opposite to the adhesive sheet 1. For example, the surface 2a is in contact with the first surface 1a of the adhesive sheet 1. The surface 2a of the optical film 2 is subjected to a surface modification treatment. According to the surface 2a subjected to the surface modification treatment, there is a tendency to improve the anchoring force between the adhesive sheet 1 and the optical film 2. As the surface modification treatment, the surface modification treatment described above for the adhesive sheet 1 can be cited.
[0167] The surface 2a is preferably subjected to a corona treatment as a surface modification treatment. When the surface 2a is subjected to a corona treatment, the conditions such as the discharge amount can be appropriately adjusted within the range described above for the pressure-sensitive adhesive sheet 1, for example.
[0168] As described above, the optical film 2 includes at least one selected from a polarizing film and a phase difference film. The optical film 2 may be a laminated film including a polarizing film and / or a phase difference film. The optical film 2 may include a film made of glass. However, the optical film 2 is not limited to the above examples.
[0169] The polarizing film includes a polarizer. Typically, the polarizing film includes a polarizer and a protective film (transparent protective film). The protective film is, for example, arranged in contact with the main surface (surface with the widest area) of the polarizer. The polarizer can be arranged between two protective films. The protective film can be arranged on at least one side of the polarizer.
[0170] The polarizer is not particularly limited, and examples thereof include: a polarizer obtained by adsorbing a dichroic substance such as iodine and a dichroic dye on a hydrophilic polymer film such as a polyvinyl alcohol film, a partially formalized polyvinyl alcohol film, and a partially saponified film of an ethylene-vinyl acetate copolymer, and then uniaxially stretching the film; a polyene oriented film such as a dehydrated product of polyvinyl alcohol and a dehydrochlorinated product of polyvinyl chloride, etc. Typically, the polarizer is formed of a polyvinyl alcohol film (polyvinyl alcohol films include partially saponified films of ethylene-vinyl acetate copolymers) and a dichroic substance such as iodine.
[0171] The thickness of the polarizer is not particularly limited, for example, it is 80 μm or less, it can be 50 μm or less, 30 μm or less, 25 μm or less, and further, it can be 20 μm or less. The lower limit of the thickness of the polarizer is not particularly limited, for example, it is 1 μm or more, it can be 5 μm or more, 10 μm or more, and further, it can be 15 μm or more. The dimensional change of the thin polarizer (for example, the thickness is 20 μm or less) is suppressed, which can contribute to the durability of the optical laminate, especially the durability at high temperature.
[0172] As the material of the protective film, for example, a thermoplastic resin having excellent transparency, mechanical strength, thermal stability, moisture barrier, isotropy, etc. can be used. Specific examples of such thermoplastic resins include cellulose resins such as cellulose triacetate, polyester resins, polyethersulfone resins, polysulfone resins, polycarbonate resins, polyamide resins, polyimide resins, polyolefin resins, (meth)acrylic resins, cyclic polyolefin resins (norbornene resins), polyarylate resins, polystyrene resins, polyvinyl alcohol resins, and mixtures thereof. The material of the protective film can be a thermosetting resin or ultraviolet curing resin such as (meth)acrylic acid, urethane, acrylic urethane, epoxy, silicone, etc. In the case where the polarizing film has two protective films, the materials of the two protective films can be the same or different from each other. For example, a protective film formed of a thermoplastic resin can be bonded to one main surface of the polarizer via an adhesive, and a protective film formed of a thermosetting resin or an ultraviolet curing resin can be bonded to the other main surface of the polarizer. The protective film can contain one or more arbitrary additives. Examples of the additive include ultraviolet absorbers, antioxidants, lubricants, plasticizers, release agents, anti-coloring agents, flame retardants, nucleating agents, antistatic agents, pigments, and colorants.
[0173] It should be noted that the film containing (meth) acrylic resin has a tendency to have a low bonding strength with the adhesive sheet. However, in the present embodiment, by making the adhesive sheet 1 satisfy the above-mentioned requirements (1) or (2). Even in the case where the surface of the protective film containing (meth) acrylic resin is equivalent to the surface 2a of the optical film 2, the anchoring force between the adhesive sheet 1 and the optical film 2 can be adjusted to a sufficiently high value.
[0174] The thickness of the protective film can be appropriately determined, and is generally about 10 to 200 μm from the perspectives of strength, workability such as handling properties, and thin film properties.
[0175] The polarizer and the protective film are usually bonded together via a water-based adhesive or the like. Examples of the water-based adhesive include isocyanate adhesives, polyvinyl alcohol adhesives, gelatin adhesives, vinyl latex, water-based polyurethane, and water-based polyester. Other adhesives other than the above-mentioned adhesives include ultraviolet curing adhesives and electron beam curing adhesives. Electron beam curing polarizer adhesives show suitable adhesion to various protective films. The adhesive may also contain a metal compound filler.
[0176] In the polarizing film, a retardation film or the like may be formed on the polarizer instead of the protective film. Another protective film or a retardation film or the like may be provided on the protective film.
[0177] The protective film may be provided with a hard coating layer on the surface opposite to the surface bonded to the polarizer, and may be subjected to treatment for the purpose of anti-reflection, anti-blocking, diffusion, anti-glare, etc.
[0178] The polarizing film may be a circular polarizing film.
[0179] As the retardation film, a film obtained by stretching a polymer film or a film obtained by orienting and fixing a liquid crystal material can be used. The retardation film has birefringence in the plane and / or in the thickness direction, for example.
[0180] The phase difference film includes a phase difference film for antireflection (refer to Japanese Patent Application Publication No. 2012-133303
[0221] ,
[0222] , and
[0228] ), a phase difference film for viewing angle compensation (refer to Japanese Patent Application Publication No. 2012-133303
[0225] and
[0226] ), and a tilted orientation phase difference film for viewing angle compensation (refer to Japanese Patent Application Publication No. 2012-133303
[0227] ).
[0181] The specific structure of the retardation film, such as the retardation value, the arrangement angle, the three-dimensional birefringence, whether it is a single layer or a multilayer, etc., is not particularly limited, and a known retardation film can be used.
[0182] The thickness of the retardation film is preferably 20 μm or less, more preferably 10 μm or less, further preferably 1 to 9 μm, particularly preferably 3 to 8 μm.
[0183] The phase difference film may include, for example, a quarter wave plate and / or a half wave plate in which a liquid crystal material is oriented and fixed.
[0184] (Characteristics of Optical Laminated Body)
[0185] As described above, in the present embodiment, the adhesive sheet 1 satisfies the requirement (1) or (2), and therefore, there is a tendency that the anchoring force F between the adhesive sheet 1 and the optical film 2 is large. The anchoring force F is, for example, 10.0 N / 25 mm or more, and may be 11.0 N / 25 mm or more, 12.0 N / 25 mm or more, 13.0 N / 25 mm or more, 14.0 N / 25 mm or more, 15.0 N / 25 mm or more, 16.0 N / 25 mm or more, and may further be 17.0 N / 25 mm or more. Preferably, the anchoring force F is greater than 16.0 N / 25 mm. When the anchoring force F is large to this extent, the peeling between the adhesive sheet 1 and the optical film 2 can be sufficiently suppressed. The upper limit of the anchoring force F is not particularly limited, and may be, for example, 50 N / 25 mm or less, and may be 30 N / 25 mm or less.
[0186] The anchoring force F of the adhesive sheet 1 and the optical film 2 can be measured by the following method. First, the optical laminate 10 to be evaluated is cut into a width of 25 mm × a length of 150 mm to make a test piece. Next, the entire surface of the optical film 2 possessed by the test piece is superimposed on the stainless steel test plate via a double-sided tape, and a 2 kg roller is reciprocated once to press them together. Next, the adhesive sheet 1 possessed by the test piece is superimposed on the evaluation sheet, and a 2 kg roller is reciprocated once to press them together. The evaluation sheet has a size of 30 mm in width × 150 mm in length, and is not particularly limited as long as it does not peel off from the adhesive sheet 1 during the test. As an evaluation sheet, for example, an ITO film (125Tetoraito OES (manufactured by Oike Industries, Ltd.) etc.) can be used. Next, using a commercially available tensile testing machine, the pressure-sensitive adhesive sheet 1 was peeled off from the optical film 2 at a peeling angle of 180° and a tensile speed of 300 mm / min while holding the evaluation sheet, and the average value of the peeling force at this time was determined as the anchoring force F between the pressure-sensitive adhesive sheet 1 and the optical film 2. It should be noted that the above test was performed in an atmosphere of 23°C.
[0187] As described above, in the present embodiment, the adhesive sheet 1 satisfies the requirement (1) or (2), and therefore, there is a tendency that the corrosion of the conductive layer can be suppressed even when the adhesive sheet 1 is in contact with a conductive layer such as an ITO layer. As an example, the surface resistance value R of the optical laminate 10 obtained by the following test 2 is 250 (Ω / □) relative to the surface resistance value R obtained by the following test 1 i (Ω / □) Ratio R 250 / R i It is preferably 3.0 or less. 250 / R i The value can be used as an indicator of the susceptibility of corrosion of the ITO layer caused by the adhesive sheet 1 .
[0188] Test 1: The adhesive sheet 1 of the optical laminate 10 (specifically, the second surface 1b of the adhesive sheet 1) is adhered to the ITO layer of the alkali-free glass having an amorphous ITO layer formed on the surface. The adhesive sheet 1 is placed in an autoclave at 50°C and 5 atmospheres (absolute pressure) for 15 minutes to homogenize the bond between the ITO layer and the adhesive sheet 1, so that the adhesive sheet 1 is closely attached to the ITO layer. The surface resistance value R of the ITO layer of the obtained evaluation sample is measured. i (Ω / □).
[0189] Test 2: The ITO layer and the adhesive sheet 1 were homogenized in an autoclave by the same method as in Test 1 to obtain an evaluation sample. The evaluation sample was treated at 65°C and 95% RH for 250 hours under atmospheric pressure. The surface resistance value R of the ITO layer of the evaluation sample after treatment was measured. 250 (Ω / □).
[0190] In Tests 1 and 2, the ITO layer can be produced by sputtering. The Sn ratio of ITO contained in the ITO layer (weight of Sn atoms / (weight of Sn atoms+weight of In atoms)) is, for example, 3 wt%.
[0191] R 250 / R i It is preferably 3 or less, and may be 2.5 or less, 2 or less, 1.5 or less, and further may be 1.3 or less. 250 / R i For example, greater than 1.0.
[0192] Another example of the optical layered body of the present embodiment is shown in Figure 5 . Figure 5 The optical laminate 11 has a laminated structure in which the adhesive sheet 1A, the optical film 2A, the adhesive sheet 1B, and the optical film 2B are laminated in this order. The optical laminate 11 may have a structure in which the base sheet used when producing the adhesive sheet 1A is laminated on the adhesive sheet 1A.
[0193] In the optical laminate 11, typically, the optical film 2A is a phase difference film, and the optical film 2B is a polarizing film. The adhesive sheet 1B functions as an interlayer adhesive between the optical films 2A and 2B. The adhesive sheet 1B may be one using a known adhesive.
[0194] The optical layered bodies 10 and 11 of the present embodiment can be distributed and stored in the form of a roll body in which a belt-shaped optical layered body is rolled up, or in the form of a single sheet-shaped optical layered body.
[0195] Another example of the optical layered body of the present embodiment is shown in Figure 6 . Figure 6 The optical laminate 12 comprises the above-mentioned adhesive sheet 1 and a conductive layer 3 comprising a metal oxide. The adhesive sheet 1 is preferably in direct contact with the conductive layer 3. Figure 6 In the example of FIG. 1 , the second surface 1 b of the adhesive sheet 1 is in contact with the conductive layer 3 .
[0196] The optical laminate 12 further includes, for example, an optical film 2 and a substrate 4. The optical laminate 12 has a laminate structure in which the optical film 2, the pressure-sensitive adhesive sheet 1, the conductive layer 3, and the substrate 4 are laminated in this order. A specific example of the substrate 4 is a glass substrate.
[0197] (Conductive layer)
[0198] The metal oxide contained in the conductive layer 3 is, for example, a composite oxide, such as indium zinc composite oxide (IZO), indium gallium zinc composite oxide (IGZO), indium gallium composite oxide (IGO), indium tin composite oxide (ITO), antimony tin composite oxide (ATO), etc.
[0199] Typically, the optical laminate of this embodiment can be used for an image display device. The image display device can be an organic EL display or a liquid crystal display. However, the image display device is not limited to the above examples. The image display device can also be a field luminescence (EL) display, a plasma display (PD), a field emission display (FED: Field Emission Display), etc. The image display device can be used for household appliances, in-vehicle uses, public information displays (PID) uses, etc.
[0200] Example
[0201] Hereinafter, the present invention will be described in more detail by way of examples. However, the present invention is not limited to the examples shown below.
[0202] [Release liner A]
[0203] 30 parts by weight of addition reaction curing silicone (LTC761 containing hexenyl polysiloxane, 30% toluene solution, manufactured by Dow Corning Toray), 0.9 parts by weight of release control agent (BY24-850 containing unreacted silicone resin, manufactured by Dow Corning Toray), 2 parts by weight of curing catalyst (SRX212 containing platinum catalyst, manufactured by Dow Corning Toray), and 1:1 volume ratio of toluene / hexane mixed solvent as diluent were mixed to obtain a silicone release agent composition. The concentration of silicone solid content in the release agent composition was 1.0% by weight. Next, the release agent composition was applied to one side of a liner substrate (Lumirror XD500P as a polyester film, 75 μm thick) using a wire bar, and heated at 130°C for 1 minute to prepare a release liner A having a release layer (60 nm thick) on one side.
[0204] [Release liner B]
[0205] A release liner B having a release layer (thickness 120 nm) on one surface was prepared by the same method as the release liner A except that the thickness of the release agent composition applied to the liner substrate was changed.
[0206] [Monomer slurry A1]
[0207] 99 parts by weight of n-butyl acrylate (BA), 1 part by weight of 4-hydroxybutyl acrylate (HBA), 0.2 parts by weight of acrylic acid (AA), 0.05 parts by weight of 1-hydroxycyclohexyl-phenyl ketone (Omnirad 184, manufactured by IGM Resins BV) and 0.05 parts by weight of 2,2-dimethoxy-1,2-diphenylethane-1-one (Omnirad 651, manufactured by IGM Resins B.V.) as photopolymerization initiators were placed in a four-necked flask and irradiated with ultraviolet rays in a nitrogen atmosphere to obtain a partially photopolymerized monomer syrup A1. The ultraviolet rays were irradiated until the viscosity of the liquid in the flask (measurement conditions: BH viscometer No. 5 rotor, 10 rpm, measurement temperature 30°C) reached about 20 Pa·s.
[0208] [Monomer slurries A2 to A4]
[0209] Except that the monomers used were changed as shown in Table 1, monomer syrups A2 to A4 were prepared by the same method as that for monomer syrup A1.
[0210] [Table 1]
[0211]
[0212] The abbreviations in Table 1 are as follows.
[0213] BA: n-butyl acrylate
[0214] HBA: 4-Hydroxybutyl Acrylate
[0215] AA: Acrylic acid
[0216] [Adhesive compositions C1 to C4]
[0217] Next, the monomer syrup, the crosslinking agent, and the anticorrosive agent were mixed so as to have the compositions shown in Table 2 below, thereby obtaining adhesive compositions C1 to C4.
[0218] [Table 2]
[0219]
[0220] The abbreviations in Table 2 are as follows.
[0221] NDDA: 1,9-nonanediol diacrylate
[0222] 9591F: Acid anhydride group-containing oligomer type silane coupling agent (manufactured by Shin-Etsu Chemical Co., Ltd., X-24-9591F)
[0223] (Example 1)
[0224] The adhesive composition C1 was applied to the release layer of the release liner A using an applicator to form a coating layer (thickness 20 μm). Next, the release liner B was arranged on the formed coating layer to obtain the first laminate. The release liner B was arranged so that the release layer and the coating layer were in contact. Next, the coating layer was exposed to light at an illumination of 2.5 mW / cm 2 The coating layer was photocured by irradiating the release liner A in the first laminate with ultraviolet light (black light source) for 640 seconds to form a second laminate consisting of the release liner A, the adhesive sheet (thickness 20 μm) and the release liner B.
[0225] Next, the release liner B was peeled off from the second laminate and the discharge amount was 61 W / m 2 The exposed surface (first surface) of the pressure-sensitive adhesive sheet was subjected to a corona treatment. In this way, a pressure-sensitive adhesive sheet of Example 1 was obtained.
[0226] (Example 2)
[0227] A PSA sheet of Example 2 was obtained by the same method as in Example 1 except that PSA composition C2 was used.
[0228] (Examples 3 and 4)
[0229] PSA sheets of Examples 3 and 4 were obtained by the same method as in Example 2 except that the discharge amount of the corona treatment was changed as shown in Table 3.
[0230] (Comparative Example 1)
[0231] A PSA sheet of Comparative Example 1 was obtained by the same method as in Example 2 except that the corona treatment was not performed.
[0232] (Comparative Example 2)
[0233] A PSA sheet of Comparative Example 2 was obtained by the same method as in Comparative Example 1 except that PSA composition C3 was used.
[0234] (Example 5)
[0235] A PSA sheet of Example 5 was obtained by the same method as in Example 1 except that PSA composition C4 was used.
[0236] [Element ratio R1]
[0237] The first surface of the adhesive sheet of the embodiment and the comparative example (the surface of the second laminate in contact with the release liner B) was treated with trifluoroethanol by the above method, and the element ratio R1 of fluorine was measured. It should be noted that the narrow scan measurement of C, N, O, F, and Si elements was performed using an X-ray photoelectron spectroscopy analyzer. The measurement conditions using the X-ray photoelectron spectroscopy analyzer are as follows.
[0238] (Measurement conditions)
[0239] Device: Quantera SXM manufactured by ULVAC-PHI
[0240] X-ray source: monochromatic AlKα
[0241] X Ray setting: 100μmφ[15kV, 25W]
[0242] Photoelectron extraction angle: 45° relative to the sample surface
[0243] Correction of bond energy: Correct the peak from CC bond in C1s spectrum to 285.0 eV
[0244] Charge neutralization conditions: Combination of electron neutralization gun and Ar ion gun (neutralization mode)
[0245] [Anchoring force]
[0246] The anchoring force F between the adhesive sheets of the embodiments and comparative examples and the polarizing film was measured. The polarizing film was prepared by the following method. First, between rollers with different speed ratios, a polyvinyl alcohol film with a thickness of 80 μm was stretched to 3 times while being dyed in an iodine solution with a temperature of 30°C and a concentration of 0.3% for 1 minute. Next, it was immersed in an aqueous solution with a temperature of 60°C containing boric acid with a concentration of 4% and potassium iodide with a concentration of 10% for 0.5 minutes, while being stretched to a total stretching ratio of 6 times. Next, it was washed by immersing it in an aqueous solution with a temperature of 30°C containing potassium iodide with a concentration of 1.5% for 10 seconds, and then dried at 50°C for 4 minutes, thereby obtaining a polarizer with a thickness of 28 μm. A transparent protective film with a thickness of 30 μm formed of a modified acrylic polymer having an inner fat ring structure was bonded to one side of the polarizer using a polyvinyl alcohol-based adhesive. Furthermore, a transparent protective film having a thickness of 47 μm and a hard coating layer (HC) formed on a triacetyl cellulose film (manufactured by Konica Minolta, trade name "KC4UY") was bonded to the other side of the polarizer using a polyvinyl alcohol-based adhesive. The film was dried by heating in an oven set at 70°C for 5 minutes to produce a polarizing film. 2 The surface of the polarizing film on the side of the transparent protective film formed of a modified acrylic polymer was subjected to a corona treatment.
[0247] Next, an optical laminate was prepared by placing the polarizing film on the first surface of the pressure-sensitive adhesive sheet (the surface of the second laminate in contact with the release liner B). The polarizing film was placed so that the surface on the transparent protective film side formed of a modified acrylic polymer was in contact with the pressure-sensitive adhesive sheet.
[0248] For the optical laminate, the anchoring force F between the adhesive sheet and the polarizing film was measured by the above method. As a double-sided tape, a product name "No.531" manufactured by Nitto Denko Corporation was used. As a stainless steel test plate, a SUS304 plate (width 40 mm × length 120 mm) was used. As an evaluation sheet, an ITO film (125 Tetoraito OES, manufactured by Oike Industries) was used. As a tensile tester, an Autograph SHIMAZU AG-I 10KN (manufactured by Shimadzu Corporation) was used.
[0249] [R 250 / R i ]
[0250] First, an optical layered body was prepared by the same method as the above-mentioned method for measuring the anchoring force F. The above-mentioned Tests 1 and 2 were carried out using the obtained optical layered body to measure the surface resistance value R 250 (Ω / □) relative to surface resistance R i (Ω / □) Ratio R 250 / R i Determined. In tests 1 and 2, the ITO layer was produced by sputtering ITO on an alkali-free glass with a thickness of 0.7 mm (manufactured by Corning, trade name "EG-XG"). The Sn ratio of the ITO contained in the ITO layer (weight of Sn atoms / (weight of Sn atoms + weight of In atoms)) is 3 wt%. The glass with the ITO layer was cut into 25 mm long and 25 mm wide for use. The optical laminate was cut into 15 mm long and 15 mm wide and attached to the central part of the ITO layer of the glass with the ITO layer. Surface resistance value R i and R 250 The measurement was performed using HL5500PC manufactured by Accent Optical Technologies.
[0251] [Table 3]
[0252]
[0253] As shown in Table 3, the PSA sheets of Examples 1 to 4 satisfying the above requirement (1) and the PSA sheet of Example 5 satisfying the requirement (2) have a higher R than the comparative example. 250 / Ri The value of is small, and the corrosion of the ITO layer is small. In addition, the anchoring force F of the adhesive sheet of the example to the optical film (polarizing film) is a large value.
[0254] Industrial Applicability
[0255] The pressure-sensitive adhesive sheet of the present invention can be used for, for example, an optical layered body or an image display device.
Claims
1. An adhesive sheet, which is formed from an adhesive composition containing a monomer group and / or a polymer of the monomer group, The adhesive sheet has a first surface and a second surface facing each other, The adhesive sheet satisfies at least one of the following requirements (1) and (2), (1) In 100 parts by weight of the monomer group, the amount of the carboxyl group-containing monomer is 0.5 parts by weight or less, When the first surface is treated with trifluoroethanol, the element ratio R1 of fluorine on the first surface is greater than 0.1 atomic %; (2) The adhesive composition contains an anticorrosive agent, In 100 parts by weight of the monomer group, the amount of the carboxyl group-containing monomer is 7.0 parts by weight or less. When the first surface is treated with trifluoroethanol, an element ratio R1 of fluorine on the first surface is 0.1 atomic % or more.
2. The adhesive sheet according to claim 1, wherein When the second surface is treated with trifluoroethanol, the element ratio R2 of fluorine on the second surface is less than 0.1 atomic %.
3. The adhesive sheet according to claim 1, wherein The adhesive composition is a photocurable adhesive composition.
4. The adhesive sheet according to claim 1, wherein The content of the solvent in the adhesive composition is 5% by weight or less.
5. The adhesive sheet according to claim 1, wherein The first surface is a surface subjected to surface modification treatment.
6. The adhesive sheet according to claim 5, wherein The surface modification treatment is corona treatment.
7. The adhesive sheet according to claim 1, wherein The anticorrosive agent comprises at least one selected from silicon-containing compounds having acidic groups or anhydride groups, phosphoric acid compounds and phosphonic acid compounds.
8. The adhesive sheet according to claim 1, wherein The monomer group includes a (meth)acrylic monomer. 9 . The pressure-sensitive adhesive sheet according to claim 1 , having a thickness of 50 μm or less.
10. An optical laminate comprising: The pressure-sensitive adhesive sheet according to any one of claims 1 to 9, and an optical film comprising at least one selected from a polarizing film and a retardation film.
11. An optical layered body according to claim 10, wherein: The first surface of the pressure-sensitive adhesive sheet is in contact with the optical film.
12. The optical layered body according to claim 10, wherein: The anchoring force between the pressure-sensitive adhesive sheet and the optical film is 10.0 N / 25 mm or more.
13. An optical laminate comprising: The adhesive sheet according to any one of claims 1 to 9, and a conductive layer comprising a metal oxide.
14. The optical layered body according to claim 13, wherein: The second surface of the adhesive sheet is in contact with the conductive layer.
Citation Information
Patent Citations
Optical display device having polarizing film
JP2012133303A